Prevalence and antimicrobial resistance of Shigella flexneri serotype 2 variant in China - Cui, Xianyan; Wang, Jian; Yang, Chaojie; Liang, Beibei; Ma, Qiuxia; Yi, Shengjie; Li, Hao; Liu, Hongbo; Li, Peng; Wu, Zhihao; Xie, Jing; Jia, Leili; et al. (Frontiers in Microbiology, 2015)
Shigella flexneri serotype 2 variant (II:3,4,7,8) was isolated in 2008 and first reported in China in 2013. In the present study, epidemiological surveillance from 2003 to 2013 in China suggested that this serotype first appeared in Guangxi in 2003; it then emerged in Shanghai and Xinjiang in 2004 and in Henan in 2008. Of the 1813 S. flexneri isolates, 58 S. flexneri serotype 2 variant strains were identified. Serotype 2 variant has emerged as a prominent serotype in recent years, with 2a (32.6%), X variant (25.2%), 1a (9.4%), X (6.3%), 2b (5.4%), and 1b (3.6%). According to phenotypic and genotypic analysis, the serotype 2 variant originated from 2a to 2b. A higher antibiotic resistance rate was observed between 2009 and 2013 than that between 2003 and 2008. Among 22 cephalosporin-resistant isolates, blaTEM-1, blaOXA-1, blaCTX-3, blaCTX-14, and blaCTX-79 were detected. Among 22 fluoroquinolone-resistant isolates, a Ser80Ile mutation in parC was present in all of the isolates. Moreover, 21 isolates had three gyrA point mutations (Ser83Leu, His211Tyr, Asp87Asn, or Gly) and one isolate had two gyrA point mutations (Ser83Leu and His211Tyr). The prevalence of His211Tyr in the fluoroquinolone-resistant isolates is concerning, and the mutation was first reported in China. Besides, 22 isolates harbored the aac(6′)-Ib-cr gene, and two isolates harbored qnrS1. In view of the increased epidemic frequency and multidrug-resistant strain emergence, continuous surveillance will be needed to understand the actual disease burden and provide guidance for shigellosis.